Effect of Aluminum Addition with Nitrogen on K-Carbide Formation in Carbon-Mn Steel - Shahid Hussain ABRO (Kaunas University of Technology, 2021)
An attempt has been made in the present research work to investigate the role and influence of chemical effect of aluminum addition in the experimental steel towards the formation of k-carbides. Two steel grades were made with and without aluminum addition by induction melting furnace and were cast to ingots. Steel A has no aluminum addition and steel B has some aluminum content. These ingots were then solution heat treated on a temperature of 1200°C for 2-hours’ time and were cooled in the air. After that, they were hot rolled to drawn in plate and sheet. The small samples were cut from bulk and were then heat-treated at 800°C for 1 hour and quenched. Microstructure by OM and SEM was captured. In steel A there was no k-carbide present in the matrix and surprisingly in steel B, small fine k-carbides were present this was then confirmed by XRD later. OM, SEM, and TEM analysis revealed that the presence of k-carbides in steel B makes less dense. It was concluded that aluminum in conjunction with nitrogen forms the small nitride particles having a high melting point does not dissolve during the melting and casting such particles are known as AlN or aluminum nitride particles was observed by TEM along with EDS was the main reason to support the formation of k-carbides, these fine nano level k-carbides are orderly distributed in the steel matrix as was shown by XRD peaks.